PENGEMBANGAN SISTEM INFORMASI E-LEARNING BERBASIS WEBSITE SEBAGAI MEDIA PEMBELAJARAN - Jafrai Manalu; Rosnelli . (Universitas Negeri Medan, 2022)
AbstractThis study aims to develop an e-learning information system (website) as a learning medium. Learning media is very significant and very effective to use for teaching and learning. Researchers are trying to develop a website-based e-learning information system that can be used as an online learning media (online). The learning media in this study uses the Waterfall (Summerville) model using five stages in it, namely Requirement Definition, System and Software Design, Implementation and Unit Testing, Integration and System Testing, Operation and Maintenance. The target of this research is the teacher admin and specifically the students. The test of the Thursday-based e-learning information system by the material validator media validator and user responses showed that the site-based e-learning information system produced both a material validation score of 4.375, a media score validation of 4.43 and a user response score validation of 4.75. Testing the effectiveness of an e-learning information system based on a website that is proven from the results of class completeness of 85% which is above the classical percentage requirement of 75% so that an e-learning information system based on a web site is effectively used as a learning medium. Key Words: E-learning Information System Development, Online Learning Media, wesbiste, basic programming. AbstrakPenelitian ini bertujuan untuk mengembangkan sistem informasi e-learning (website) sebagai media pembelajaran. Media pembelajaran termasuk hal yang sangat signifikan dan sangat efektif untuk dipergunakan untuk belajar mengajar. Peneliti berusaha mengembangkan sistem informasi e-learning berbasis website yang dapat dijadikan sebagai media pembelajaran online (daring). Media pembelajaran pada penelitian ini menggunakan model Waterfall (Summerville) dengan menggunakan lima tahapan didalamnya yaitu Requirements Definition, System and Software Design, Implementation and Unit Testing, Integration and System Testing, Operation and Maintenance. Sasaran penelitian ini adalah admin guru dan secara khusus pesertadidik. Pengujian kelayakan sistem informasi e-learning berbasis wesbite oleh validator media validator materi dan respon pengguna menunjukkan bahwasanya sistem informasi e-learning berbasis website yang dihasilkan sanggat baik berdasarkan skor validasi materi 4,375, skor validasi media 4,43 dan skor validasi respon pengguna 4,75. Pengujian keefektivan terhadap sistem informasi e-learning berbasi website teruji dari hasil ketuntasan kelas sebesar 85 % yang berada diatas syarat persentase klasikal ≥ 75% sehingga sistem informasi e-learning berbasis website efektif digunakan sebagai media pembelajaran.Kata Kunci: Pengembangan Sistem Informasi E-learning, Media Pembelajaran online, wesbiste, Pemrograman dasar